Study the Causes of Work Related Stress Risk in Construction Sector in Afghanistan - Zadran, Badam Gul; Elham, Fareed Ahmad; Hamid, Abdul Rahim Abdul (Journal for Research in Applied Sciences and Biotechnology, 2023)
This study was carried out to study the causes of stress risk in the construction sector of Afghanistan. It has become a growing concern in many sectors, not to mention the construction sector. It is important to ensure that workers can perform at their best, considering the construction industry's highly competitive demands and competition. Stress risk has been identified as an important factor influencing an organization's success, as it negatively affects the organization's productivity, professionals' health and safety, efficiency, and costs. The issue of work-related stress risk in the construction sector of Afghanistan is not commonly discussed. The objectives of this study are to find the causes of work-related stress risk. Data was collected using a questionnaire survey in Afghanistan through email from construction industry professionals such as project managers, site supervisors, project engineers, quantity surveyors, and architects. The data was analyzed using frequency analysis, the average index. For the causes of work-related stress risk, the main issues were the lack of management and control over work and increasing the employee’s expectations using the standard of safety. Based on the analysis of likelihood and severity, Ninth factors were in the very high and two were neutral the high stress risk at construction site were lack management and it supports, increase in duties, lack tool and safety.